EDUKASI SEKSUAL DAN KECERDASAN SOSIAL-EMOSIONAL UNTUK REMAJA SMP DALAM MENGHADAPI MASALAH PUBERTAS - NASOKHA, SRI; Ramadhani, Okfanisa Riskia; Jamila, Tiara Rahma Sari Nur; Maharani, Lisa; Natalia, Nia; Aini, Dewi Khurun (Universitas Negeri Jakarta, 2025)
This study aims to explore the importance of sexual education and social-emotional intelligence in helping junior high school students cope with puberty-related issues. Puberty is a transitional period filled with physical, emotional, and social changes, which can often be confusing for adolescents. Proper sexual education and strong social-emotional intelligence can serve as effective tools to support adolescents in understanding and managing these changes. This research uses a quantitative approach with a Community-Based Research (CBR) methodology. In this CBR approach, the service activities emphasize active participation from the students as collaborative partners at every stage of the project. The research results indicate that psychoeducation plays a crucial role in increasing students' knowledge of sexual education and social-emotional intelligence. The data shows a significant improvement in students' scores before and after the sexual and social-emotional education program, from 11.57 to 21.54, demonstrating a notable difference following the psychoeducational intervention. Therefore, sexual psychoeducation and the development of socialemotional intelligence in schools are essential to support mental health and well-being among adolescents in facing the challenges of puberty.